PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA PERUSAKAN SEPEDA MOTOR - Hakim, Lukmanul; Ainita, Okta; Panjaitan, Justicia Tessalonika (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The act of destruction of goods in this case is a motorcycle is one form of lawlessness, which is regulated in Article 406 paragraph (1) of the Criminal Code. The problem is how criminal accountability for the perpetrators of motorcycle destruction and how the judge’s consideration in the enforcement of the verdict against the perpetrator of the motorcycle destruction crime. Data collection is based on literature studies and field studies, while data processing is done by editing methods, classification and systematization of data, then analyzed using qualitative analysis. The results of the study showed that criminal liability against the perpetrators of motorcycle destruction crimes has been proven legitimately and convinced guilty of committing criminal acts of destruction and criminally convicted defendants therefore with a prison sentence of 1 (one) year each and the basis of the judge’s consideration in the enforcement of the verdict against the perpetrator of the crime of bicycle destruction, among others, evidence, Witness statements, expert testimony, indictments and demands of the Public Prosecutor, elements that meet in the Prosecutor’s Indictment, as well as incriminating and mitigating matters in the accused